Pengaruh Pemberian Reward dan Punishment terhadap Kedisiplinan Siswa pada Mata Pelajaran Aqidah Akhlak: The Influence of Reward and Punishment on Student Discipline in Aqidah Akhlak Subjects - Habibatul, Maspupah; Nurfalah, Muhammad Syamsudin; Rustandi, Nandi; Nurmiati, Ai Siti (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
Student discipline is a critical component in Aqidah Akhlak instruction within Islamic schools, yet effective strategies to foster it remain underexplored. This study aims to examine the impact of implementing rewards and punishments on student discipline in the Aqidah Akhlak subject at MTs An-Najwa Parungkuda, Sukabumi. Employing a quantitative approach with an experimental design, the study involved total sampling of 42 students from grades VIII and IX. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed using the Spearman Rank correlation test due to non-normal data distribution. Findings revealed a very weak relationship between reward and punishment and student discipline, with a correlation coefficient of 0.224 and an effect contribution of only 0.04%. These results suggest that extrinsic behavioral interventions alone are insufficient to foster meaningful disciplinary improvements in religious educational settings, which emphasize affective and spiritual development. The study highlights the need for discipline strategies grounded in Islamic values and relational approaches between teachers and students. Limitations include the small sample size, single research location, and short duration of intervention. Future studies are encouraged to employ mixed-method or longitudinal designs to provide deeper insights into the complexities of student discipline within the Islamic education context.